Pin Size Selection for Normograde Intramedullary Pinning of Distal Humeral Fractures in the Dog. Issue 5 (20th October 2014) - Shipov, Anna; Biton, Erez; Shati, Shachar; Joseph, Rotem; Milgram, Joshua
Abstract : Objective: To determine the optimal intramedullary (IM) pin size for open and percutaneous normograde pinning of the distal humerus. Study Design: Ex vivo anatomic study. Sample Population: Sixteen canine cadavers. Methods: Sixteen pairs of forelimbs were harvested from canine cadavers weighing 25–35 kg. The craniocaudal diameter of the humeral medullary canal, at the distal 80th percentile of its length, was measured on a lateral radiograph. Forelimbs within each pair were allocated to percutaneous or open pinning techniques. Cadavers were divided into three groups based on IM pin diameter relative to the medullary canal diameter: Group 25–35%, Group 36–45%, and Group 46–55%. Pins were inserted normograde into the medial epicondyle and advanced until they exited the proximal humerus. Pin tracts were dissected and damage to soft tissue, bony structures, and location of entry and exit points were documented. The humeri were also cut at the thinnest point of the medial epicondyle and damage to the bone was evaluated. Results: There was no difference in any of the outcomes between the open and percutaneous techniques. Cortical damage was more frequent in Group 46–55% and included blanching and or fracture of the cortex of the medial epicondyle, with fracture occurring in 6/10 limbs in this group. Pins in Group 46–55% exited the farthest and most distal from the optimal exit point and were difficult to place in all limbs. Conclusion: This study supports a recommendation for open and percutaneous pinning of the humerus with IM pins 36–45% of the medullary canal diameter measured at the distal 80th percentile of humeral length.